POLICY IMPLEMENTATION OF SOLID WASTE MANAGEMENT BY THE ENVIRONMENTAL OFFICE OF BEKASI REGENCY - Rahman, Arif; Myrna, Rita; Karlina, Nina (Universitas Medan Area, 2020)
Policy implementation of solid waste management is a part of public policy to implement in order to create a safe, sound environment and public space for the people. Bekasi Regency government contributes to solid waste management in their region that they assign the Environmental Office to hold the main role in implementing the policy. Thus, this study sought to profoundly describe the policy implementation of solid waste management by the Environmental Office of Bekasi Regency. This study used qualitative approach with ?single instrumental case study? strategy by selecting a relevant case and focusing on the given phenomena and problems. The results show that policy implementation of solid waste management by the Environmental Office of Bekasi Regency has not been optimized due to the limited capacity of the Office in providing resources and budgets, creating new innovations, and influencing people?s mindset. However, it can be said that Environmental Office has been good enough in making policies and efforts for solid waste management since they have been sinergyzed with those of the above level.